The resilience of perennial grasses under two climate scenarios is correlated with carbohydrate metabolism in meristems. (26th September 2019) - Volaire, Florence; Morvan-Bertrand, Annette; Prud'homme, Marie-Pascale; Benot, Marie-Lise; Augusti, Angela; Zwicke, Marine; Roy, Jacques; Landais, Damien; Picon-Cochard, Catherine
Abstract: Extreme climatic events (ECEs) such as droughts and heat waves affect ecosystem functioning and species turnover. This study investigated the effect of elevated CO2 on species' resilience to ECEs. Monoliths of intact soil and their plant communities from an upland grassland were exposed to 2050 climate scenarios with or without an ECE under ambient (390 ppm) or elevated (520 ppm) CO2 . Ecophysiological traits of two perennial grasses ( Dactylis glomerata and Holcus lanatus ) were measured before, during, and after ECE. At similar soil water content, leaf elongation was greater under elevated CO2 for both species. The resilience of D. glomerata increased under enhanced CO2 (+60%) whereas H. lanatus mostly died during ECE. D. glomerata accumulated 30% more fructans, which were more highly polymerized, and 4-fold less sucrose than H. lanatus . The fructan concentration in leaf meristems was significantly increased under elevated CO2 . Their relative abundance changed during the ECE, resulting in a more polymerized assemblage in H. lanatus and a more depolymerized assemblage in D. glomerata . The ratio of low degree of polymerization fructans to sucrose in leaf meristems was the best predictor of resilience across species. This study underlines the role of carbohydrate metabolism and the species-dependent effect of elevated CO2 on the resilience of grasses to ECE. Abstract : The contrasting resilience of two perennial grasses under future climate scenarios was associated with carbohydrate metabolism, such as fructan polymerization in leaf meristems, that could contribute to plant dehydration tolerance.